(untitled) (International Journal of Physiotherapy, 2017)
Background: Many cricket experts have explained the pull shot technique but could not quantify the kinematics of the stroke. This study was aimed to quantify the coaching description and compare the pull shot technique of the senior, under-19 and under-16 cricket batsmen. Methods: Eighteen Malaysian national cricket batsmen were selected for this study. Two high speed video cameras were used for capturing the pull shot action and Aerial Performance Analysis Software was used for the kinematics analysis. One way ANOVA with repeated measure was applied to examine between groups difference in biomechanics of the pull shot. Results: Results showed the senior batsmen were significantly higher in the extension of the right knee (P < .03) than under-16 batsmen and the extension of the left hip (P < .04) than under-19 batsmen. The under-16 batsmen were significantly faster in the linear velocity of the left hip (P < .04) than senior and left elbow (P < .05) than under-19 batsmen. Conclusion: This study confirms some coaching descriptions such as the bat angle was lesser than the 90° and higher than the 45° degrees and straighter position of the arms at bat-ball impact. The under-16 batsmen were faster in the linear velocities of the left hip and left elbow because they used light weight bat for the execution of the pull shot than the seniors and under-19 batsmen. This study will help the coaches and cricketers to understand the kinematics of the body segments during the execution of the pull shot. Future study should be conducted to investigate the effect of the anthropometric measures on the kinematics of the pull shot.